2005
DOI: 10.1097/01.ijg.0000151887.51541.af
|View full text |Cite
|
Sign up to set email alerts
|

Level of Disagreement Between Proview??? Phosphene Tonometer and Goldmann Applanation Tonometer Intraocular Pressure Readings

Abstract: There was considerable discrepancy between Proview and GAT readings. However, regular use of the Proview tonometer significantly reduced patients' anxiety about their glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 12 publications
0
20
0
2
Order By: Relevance
“…Nine studies 124,127,137,138,168,174,176,177,198 reported on recordability, with all but one study 137 (recordability of 76%) having very high recordability percentages (91-97%). Seven studies 127,137,168,172,176,177,198 reported the reason, i.e.…”
Section: Recordabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies 124,127,137,138,168,174,176,177,198 reported on recordability, with all but one study 137 (recordability of 76%) having very high recordability percentages (91-97%). Seven studies 127,137,168,172,176,177,198 reported the reason, i.e.…”
Section: Recordabilitymentioning
confidence: 99%
“…In total, 10 studies 124,127,137,138,168,176,178,191,198,208 (50%) reported individual measures taken within 1 hour. In 12 studies (60%) the same clinical data were available for interpretation as would be available in clinical practice 124,127,133,137,138,158,162,168,172,177,205,207 and it was reported that the examiner(s) were masked to the results. 124,125,158,162,168,172,[176][177][178]205,207,208 In seven studies 125,127,172,177,178,205,208 (35%) the tonometers used were calibrated.…”
Section: Transpalpebral Tonometermentioning
confidence: 99%
See 3 more Smart Citations